If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 * 3 + 9y = 81 Multiply 9 * 3 27 + 9y = 81 Solving 27 + 9y = 81 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 9y = 81 + -27 Combine like terms: 27 + -27 = 0 0 + 9y = 81 + -27 9y = 81 + -27 Combine like terms: 81 + -27 = 54 9y = 54 Divide each side by '9'. y = 6 Simplifying y = 6
| 2(k+2)+6(k-2)=5k-2 | | .5t+15=-10 | | (7x-3)(12x-7)= | | -(2x+3)=3x+1 | | (3x-5)=2.5x+3(x-6) | | 1-10/13 | | 2x/5=5x+2/6 | | 4g-5-3-4g= | | 5n+34=-21 | | 4u=5(u-1)-3 | | 5*6*7/8 | | (2x)/5=(5x+2)/6 | | 9/3*6*4/9 | | .5x^2+.5x-6=y | | y=10/9*5+10 | | 9/3(6*4/9) | | -10z-5=-20z+1.6 | | y=10/9*4+10 | | 5x+4(-3x-5)=-22-5x | | 5-2b=3b-7b+25 | | 11/19/8/19 | | 4(x+1)-2(3x+5)=-3x+1 | | 1-8/19 | | 54.3x=29 | | 5y-6+y=15+4y-5y | | 78+y=80 | | 80+83+71+61+95+y=80 | | (5w+24)+(2w+13)=155 | | 4=-3x-8 | | 3n=27-6(n-3) | | 2x^2+19x-4.9=0 | | 80+83+71+61+95+y=78 |